Incidence and Factors of Hepatocellular Carcinoma in Hepatitis C Virus Patients Achieving Sustained Virological Response After Direct-Acting Antiviral Treatment - Kurniawan, Juferdy Kurniawan; Wicaksono, Dhaneswara Adhyatama; Yunihastuti, Evy; Masnjoer, Arif (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2024)
Background: The incidence and risk factors for Hepatocellular Carcinoma (HCC) in Hepatitis C Virus (HCV) patients who have achieved Sustained Virological Response (SVR) after Direct-Acting Antiviral (DAA) therapy are not well established. Considering there are differences in DAA types, virus genotypes, and patient profiles in Indonesia, this study was conducted to assess the incidence and factors influencing HCC in HCV patients after SVR post DAA therapy. The objective of this study to determine the incidence and factors influencing HCC in HCV patients achieving SVR after DAA treatment.Methods: Retrospective cohort study conducted at Cipto Mangunkusumo National General Hospital, sample of HCV patients had SVR after DAA therapy in 2017 – 2019, followed until 2024. Patients were screened for abdominal ultrasound, alpha-fetoprotein (AFP) and 3-phase abdominal CT scan, if indicated. Descriptive, bivariate analysis with Fisher's exact, and multivariate analysis with logistic regression were conducted.Results: Among 180 subjects, the incidence and incidence ratio of HCC is 4.4% (0.91/100PY). Significant correlation in bivariate analysis from the variables liver cirrhosis (RR 10.5; CI 95% (1. 32 – 83.5); p = 0.0073) and type 2 DM (RR 8.47; CI 95% (2, 3 – 31.1) p = 0.0048). In multivariate analysis, there was significant correlation from type 2 DM variable (aRR 3.1; CI 95% (0.86 – 3.83); p=0.002).Conclusion: The incidence of HCC reaches 4.4% of the total population. Type 2 DM has significant correlation with the incidence of HCC in HCV patients who achieve SVR after DAA treatment.